Footprints of innate immune activity during HIV-1 reservoir cell evolution in early-treated infection - Sun,W; Gao,C; Gladkov,GT; Roseto,I; Carrere,L; Parsons,EM; Gasca-Capote,C; Frater,J; Fidler,S; Yu,XG; Lichterfeld,M; Sandström,E; et al. (Journal of Experimental Medicine, 2024)
Antiretroviral treatment (ART) initiation during the early stages of HIV-1 infection is associated with a higher probability of maintaining drug-free viral control during subsequent treatment interruptions, for reasons that remain unclear. Using samples from a randomized-controlled human clinical trial evaluating therapeutic HIV-1 vaccines, we here show that early ART commencement is frequently associated with accelerated and efficient selection of genome-intact HIV-1 proviruses in repressive chromatin locations during the first year after treatment initiation. This selection process was unaffected by vaccine-induced HIV-1-specific T cell responses. Single-cell proteogenomic profiling demonstrated that cells harboring intact HIV-1 displayed a discrete phenotypic signature of immune selection by innate immune responses, characterized by a slight but significant upregulation of HLA-C, HLA-G, the IL-10 receptor, and other markers involved in innate immune regulation. Together, these results suggest an accelerated immune selection of viral reservoir cells during early-treated HIV-1 infection that seems at least partially driven by innate immune responses.